Five differentially expressed proteins identified to serve as potential blood biomarkers for schizophrenia screening based on proteomics - Li, Ronghua; Fu, Xiaoqian; Li, Chuanwei; Yuan, Lian; Liu, Yaozhi; Yang, Lin; Fang, Xiaojia; Zhang, Xiaobin; Zhang, Guangya; Du, Xiangdong (Frontiers in Psychiatry, 2026)
IntroductionSchizophrenia is a multifactorial neuropsychiatric disorder characterized by a wide range of debilitating symptoms and relatively poor clinical outcome, bringing a huge burden of disease. However, the underlying pathological mechanism of this disease remains unclear. We aimed to use mass spectrometry to complete proteomics analysis to find biomarkers related to schizophrenia in peripheral blood, which can provide some biomarker for the pathology, diagnosis or treatment of schizophrenia and the focus of future research. MethodsThis study was a cross-sectional case-control study involving 46 patients with schizophrenia and 43 healthy controls. All subjects provided early morning fasting cubital venous blood, completed the collection of general demographic data and clinical scale evaluation. At last, the blood samples of all subjects were subjected to mass spectrometry analysis, combined with bioinformatics analysis, to identify and screen differential proteins. ResultsUsing nominal P<0.05 (uncorrected) and fold change > 1.5 or < 0.67, 34 proteins were prioritized, among which 22 proteins were up-regulated and 12 were down-regulated; these candidates require false discovery rate controlled verification. Gene ontology over-representation analysis suggested trends in cellular component organization and cell adhesion molecule binding, with no false discovery rate correction. Kyoto encyclopedia of genes and genomes functional enrichment analysis showed that the differential proteins were mainly involved in mitogen-activated protein kinase signaling pathways. DiscussionOur research indicates that neural cell adhesion molecule L1, integrin alpha-M, alpha-actinin-1, filamin-A and profilin-1 which are associated with cytoskeleton, synapse and immunity were preliminarily screened as candidate protein markers for schizophrenia. Moreover, mitogen-activated protein kinase signaling pathway may be related to the pathology of schizophrenia, and PI3K-Akt signaling pathway may be related to the efficacy and side effects of antipsychotic drugs.